Vagococcus salmoninarum II—qPCR, tropism and egg‐associated transmission. Issue 3 (6th February 2020) - Standish, Isaac; Leis, Eric; Erickson, Sara; McCann, Rebekah; Puzach, Corey; Katona, Ryan; Lark, Ellen; Bailey, Jennifer; Kleman, Eric; Buening, Jorge; Edwards, Carey; Loch, Thomas; et al.
Abstract: Vagococcus salmoninarum was identified as the causative agent of a chronic epizootic in broodstock "coaster" brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery. The epizootic spanned more than a year, was unresponsive to multiple florfenicol treatments, and resulted in >50% mortality of the affected fish. The decision was made to cull the remaining fish during spawning, which presented an opportunity to more thoroughly examine V. salmoninarum sampling methods, organ tropism and vertical transmission. A newly developed qPCR targeting the pheS gene was used in concert with bacterial culture to show that V. salmoninarum indeed disproportionately affects females and has a tropism for female reproductive tissues. The study demonstrates that some female reproductive tissues (e.g. ovarian fluid, unfertilized eggs) are also an effective option for non‐lethal detection. Despite the widespread presence of V. salmoninarum in ovarian fluid and on egg surfaces, we found no evidence of intra‐ova transmission.